Wyznaniowe zróżnicowanie kultury gospodarczej. O ideologicznym nadużyciu znanej tezy - Dylus , Aniela (Człowiek i Społeczeństwo, 2014)
More than one hundred years ago, Max Weber agued that the Protestant religion, particularly the religious ideas of Calvinism and the Puritan ethic, played a positive role in creating the capitalistic spirit. The article hereby attempts to show that this thesis (the Protestant Ethic Thesis) gradually evolved into different stereotypes. It also appeared to be especially prone to some ideological abuse. The description of these stereotypes and different forms of abuse has been preceded with attempts to answer some questions such as: Is the cultural context of economic life really differentiated with regard to religious ideas? Is Max Weber’s thesis timeless? In fact, the results of various kinds of research allow to falsify the thesis given above. It is the real religious faith as such and not its content that is economically significant. However, there are some cultural differences between Catholics and Protestants that are determined by their religious faith. These differences concern rather e.g. their different focus on the value hierarchy or significance attached to satisfying needs.